Morbid Obesity with Severe Hypertension: A Clinical Challenge - Bobbity Deepthi; Sriram Krishnamurthy; Pediredla Karunakar; Reena Gulati (Wolters Kluwer Medknow Publications, 2022)
Background: Morbid obesity is a growing concern among children and adolescents, and is complicated by multitude of morbidities such as diabetes, hypertension, metabolic syndrome, and sleep disturbances. Obesity-related hypertension is a distinct phenotype in children and adolescents and needs extensive evaluation to look for underlying etiology. Clinical Description: We report a case of acute nephritic syndrome who presented in hypertensive emergency, was found to have morbid obesity, evaluated and diagnosed as Prader-Willi syndrome with metabolic syndrome and obstructive sleep apnea (OSA). After initial stabilization, relevant blood investigations and urinalysis confirmed the diagnosis of poststreptococcal glomerulonephritis. A carefully planned evaluation identified multiple morbidities of severe obesity and determinants for the chronic hypertension. Management: The morbid obesity necessitated a thorough evaluation for etiology and complications. The child was managed for hypertensive emergency and started on multiple anti-hypertensives. The identification and management of OSA led to better control of hypertension. A holistic plan was formulated to address other medical issues including the metabolic syndrome, deranged lipid profile, impaired social cognition, and behavioral issues. Conclusion: Obesity-related chronic hypertension was unveiled in our patient by an acute hypertensive emergency. This case underscores the importance of screening for hypertension in chronic conditions such as obesity and sleep-disordered breathing at every clinical encounter and also the need for a holistic multidisciplinary approach for managing morbid obesity.